The first-in-class bispecific antibody IBI318 (LY3434172) targeting PD-1 and PD-L1 in patients with advanced tumors: a phase Ia/Ib study - Dan-Yun Ruan; Xiao-Li Wei; Fu-Rong Liu; Xi-Chun Hu; Jian Zhang; Dong-Mei Ji; Ding-Zhi Huang; Yan-Qiu Zhao; Hong-Min Pan; Wang-Jun Liao; Kun-Yu Yang; Nong Xu; et al. (Journal of Hematology & Oncology)
Abstract Background There is an unmet clinical need to enhance the response rate and safety of anti-PD-1/PD-L1-based cancer immunotherapy (IO). Herein, we presented the clinical study of IBI318 (LY3434172), a first-in-class bispecific antibody (bsAb) targeting PD-1 and PD-L1, in patients with advanced tumors. Methods In this open-label, multicenter Phase Ia/Ib study of IBI318, the Phase Ia involved dose escalation and a safety dose expansion, while the Phase Ib focused on preliminary safety and efficacy evaluation in non-small cell lung cancer (NSCLC) and nasopharyngeal carcinoma (NPC). In Phase Ia, patients with advanced tumors received IBI318 doses ranging from 0.3 to 1200 mg every two weeks (Q2W) to determine the recommended Phase 2 dose (RP2D). In Phase Ib, NSCLC or NPC patients from five cohorts with varying treatment histories received IBI318 at the RP2D. The primary endpoint was safety and the secondary endpoints included efficacy assessed by investigators according to RECIST v1.1, pharmacokinetics, immunogenicity, and pharmacodynamics. Results From February 11, 2019, to January 25, 2022, a total of 103 eligible patients were enrolled (Phase Ia, n = 55; Phase Ib, n = 48). The median follow-up was 10.1 months (range 0.7–28.6). The RP2D was determined to be 300 mg Q2W. Treatment-related adverse events (TRAEs) of any grades occurred in 88 patients (85.4%), while 10 patients (9.7%) experienced grade ≥ 3 TRAEs. The objective response rate (ORR) was 15.5% and the disease control rate (DCR) was 49.5% in all patients. In Phase Ib, the confirmed ORR was 45.5% in treatment-naïve NSCLC patients and 30.0% in IO-naïve NPC patients who had failed or were intolerant to platinum-based treatments. Conclusions IBI318 demonstrated a favorable safety profile and preliminary efficacy in treatment-naïve NSCLC and IO-naïve NPC patients. Further clinical studies are needed to assess the full therapeutic potential of PD-1/PD-L1 dual inhibition with bsAbs.